Ophthalmic Bioengineering. Review - V. O. Ponomarev; A. E. Zhdanov; P. V. Luzhnov; I. D. Davydova; E. N. Iomdina; A. V. Lizunov; A. Yu. Dolganov; S. A. Ivliev; M. A. Znamenskaya; V. N. Kazajkin; V. I. Borisov; E. O. Filatova (Oftalʹmologiâ)
This article published the materials of the round table “Bioengineering in ophthalmology” (OphthalmicBioengineering), held on May 13, 2021 as part of the international conference Ural Symposium on Biomedical Engineering, Radioelectronics and Information Technology (USBEREIT). USBEREIT is held under the auspices of the IEEE Engineering in Medicine and Biology Society. The article presents reports on: metrological aspects of registration of tonometric and electrophysiological signals in ophthalmic diagnostics; approaches to modeling the processes of pulse blood filling of the eye with the determination of hemodynamic parameters; retinotoxicity based on electrophysiological signals; analysis of electrophysiological signals in the frequency-time domain and its application in clinical practice; extraction and analysis of specialized data obtained from the electrophysiological medical device; as well as diagnosing retinal diseases based on optical coherence tomography using machine learning.